Ethnomedicinal plants of Assam, India: A review on bioactive metabolites, therapeutic potential and future perspectives - Satya, ND; Ruby, D; Manoj, B (Plant Science Today, 2026)
Ethnomedicinal plants are integral to the traditional healthcare systems of indigenous communities in Assam, India. Groups such as the Bodo, Mising, Dimasa, Karbi, Rabha and Deori have long utilized a diverse range of local flora to treat ailments ranging from infections and fevers to chronic inflammatory and metabolic disorders. This review synthesizes current knowledge on bioactive metabolites derived from ethnomedicinal plants of Assam and evaluates their therapeutic relevance and future research prospects. A systematic literature survey was conducted using major scientific databases including Scopus, Web of Science, PubMed and Google Scholar. A total of 139 studies were included in the final analysis, documenting 86 ethnomedicinal plant species belonging to 48 families, traditionally used to treat major ailment categories, with gastrointestinal disorders, dermatological conditions and inflammatory diseases being the most frequently reported. Phytochemical investigations revealed the presence of diverse classes of bioactive metabolites, including alkaloids, flavonoids, phenolics, terpenoids, glycosides and saponins. Several species demonstrated significant pharmacological activities such as antioxidant, antimicrobial, anti-inflammatory, antidiabetic and anticancer properties, corroborating traditional therapeutic claims. The review highlights critical research gaps, including limited metabolite profiling, lack of clinical validation and concerns regarding sustainable utilization. Future perspectives emphasize the need for integrative ethnobotanical-phytochemical approaches, advanced metabolomics and conservation-oriented strategies to harness Assam’s ethnomedicinal wealth for drug discovery and sustainable healthcare development. Integrating traditional knowledge with modern scientific approaches can both preserve cultural heritage and contribute meaningfully to global drug discovery and sustainable healthcare solutions.